CARDIOVASCULAR BIOMARKERS, TYG INDEX AND TG/HDL-C RATIO IN SUBCLINICAL HYPOTHYROIDISM PATIENTS - Abdullah, Barhav; Salih , Sherwan (Science Journal of University of Zakho, 2025)
Subclinical hypothyroidism (SCH) is characterized by exhibiting a normal value of free thyroxine (T4) and excessive blood thyroid-stimulating hormone (TSH) concentration. SCH may be regarded as a prevalent concern of the emergence of overt hypothyroidism and cardiovascular disease (CVD). Disturbance in irisin, visfatin, NADPH oxidase, triglyceride/high-density lipoprotein-cholesterol (TG/HDL-c) ratio, and triglyceride glucose (TyG) index are associated with an increased cardiometabolic risk. The present study aimed to investigate serum levels of visfatin, irisin, NADPH oxidase (gp91phox), TyG index, TG/HDL-c ratio, and anti-TPO in patients with SCH in comparison to apparently healthy individuals. A study of the case-control method was carried out at Vin Specialist Laboratory, Kurdistan Region, Iraq, involving 146 subjects, including 73 newly diagnosed subclinical hypothyroid patients and 73 healthy controls. Biochemical tests such as glucose, TSH, FT4, FT3, Anti-Thyroid Peroxidase (anti-TPO), TG, and HDL-C were analyzed using Cobas6000 (Roche), whereas, enzyme-linked immunosorbent assay was conducted to estimate the value of serum visfatin, NADPH oxidase (gp91phox) and irisin. There was significantly a higher mean serum level of NADPH oxidase in 73 patients with SCH compared to that of 73 healthy individuals (8.73±2.89 ng/mL, 6.41±1.23 ng/mL, P=0.004). Mean serum levels of visfatin (41.29±8.16 ng/ml) and NADPH oxidase (8.73±2.89 ng/ml) were elevated in subclinical hypothyroid patients in comparison with healthy individuals with significant differences (p<0.001 and p=0.001), whereas, the mean serum level of irisin (15.78±2.64 ng/ml) was reduced in the SCH patients compared to healthy individuals (p=<0.001). The study found that, in contrast to healthy control individuals, patients with subclinical hypothyroidism had lower levels of serum irisin and higher mean values of TG/HDL-C, visfatin, TyG index, and NADPH oxidase